Indicators of Arabic Writing Ability Based on CEFR: A Comprehensive Analysis and Its Implications in Indonesia - Nurdianto, Talqis; Febriani, Erma; Aulia, Nova; Khasanah, Zulaikha Nur; Huda, M. Miftakhul; Firdaus, Mochammad; Zainuddin, Ghazali (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2026)
This study aims to comprehensively analyse  the indicators of Arabic writing ability based on the Common European Framework of Reference for Languages (CEFR) at each level. This study outlines the can-do descriptors for writing skills, covering aspects of grammar, vocabulary, coherence, and cohesion expected at each stage of proficiency. This research  also identifies significant challenges and opportunities in the implementation of CEFR in Arabic writing learning in Indonesia, taking into account unique linguistic and pedagogical contexts. The method used is descriptive analysis on primary data. Data collection was used a documentation method, and data analysis was carried out related to Arabic writing skills at each level. The results of the research are presented in a descriptive form. The results of this study mention the indicators of each level; A1 level is able to write personal information and make very simple short note messages, while A2 is able to write simple notes and messages on familiar topics, as well as compose short personal letters and simple paragraphs. At the B1 level, you can produce simple connected texts on familiar topics or personal interests, as well as prepare reports with basic structure and argumentation., while B2 is capable of producing clear and detailed texts on various subjects, comprehensively formulating arguments, and explaining points of view comprehensively. And C1 can produce clear, structured, and detailed texts on complex subjects, including essays with effective argumentation and sophisticated language, while C2 can produce clear, flowing, and complex texts with appropriate styles and logical structures, as well as coherently summarize information from various sources.